Synthesis and Dielectric Properties of Bi4-xNdxTi3O12 obtained by solution combustion synthesis - Al-Amani, Umar (2010)
Bismuth neodymium titanate, BNdT (Bi4-xNdxTi3O12 where x = 0.2, 0.4, 0.6, 0.8, 1.0) powders were synthesized via solution combustion synthesis for ferroelectric memory devices. *more details in complete paper.